Vibration suppression of scaled-down towers in offshore wind power based on pendulum tuned particle damper - Wangqiang Xiao; Zhipeng Xie; Wuping Yao; Fei Mo; Zhiqin Cai (PLoS ONE, 2025)
This paper presents a method for suppressing vibrations in a scaled wind turbine tower subjected to wind loads. The proposed approach employs a composite damping system—the Pendulum Tuned Particle Damper (PTPD). A mathematical model of the damping system was developed by deriving the equations of motion for the pendulum damper using Lagrange’s method, while accounting for the damping force exerted by particles. The optimal damper parameters were identified through numerical simulations. Through the method of the finite element-discrete element (FEM-DEM) coupled vibration reduction simulations tailored to the tower’s vibration characteristics, we demonstrated that 10 mm ferrous particles were optimal, resulting in an 81.1% vibration reduction. Experimental results confirmed the influence of the damper mass ratio, configuration, particle material, and particle size on damping effectiveness, thus validating the simulation methodology.